First Robotic SPECT for Minimally Invasive Sentinel Lymph Node Mapping - Fuerst, Bernhard; Sprung, Julian; Pinto, Francisco; Frisch, Benjamin; Wendler, Thomas; Simon, Herve; Mengus, Laurent; Van Den Berg, Nynke S.; Van Der Poel, Henk G.; Van Leeuwen, Fijs W. B.; Navab, Nassir (IEEE Transactions on Medical Imaging, 2016)
In this paper we present the usage of a drop-in gamma probe for intra-operative Single-Photon Emission Computed Tomography (SPECT) imaging in the scope of minimally invasive robot-assisted interventions. The probe is designed to be inserted and reside inside the abdominal cavity during the intervention. It is grasped during the procedure using a robotic laparoscopic gripper enabling full six degrees of freedom handling by the surgeon. We demonstrate the first deployment of the tracked probe for intra-operative in-patient robotic SPECT enabling augmented-reality image guidance. The hybrid mechanical-and image-based in-patient probe tracking is shown to have an accuracy of 0.2 mm. The overall system performance is evaluated and tested with a phantom for gynecological sentinel lymph node interventions and compared to ground-truth data yielding a mean reconstruction accuracy of 0.67 mm.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Endoscopy/laparoscopy; image-guided treatment; SPECT; surgical guidance/navigation